KEPADATAN POPULASI HAMA BOLENG (Cylas formicarius) (Coleoptera: Curculionidae) PADA TANAMAN UBI JALAR DI TALUAK DALAM KANAGARIAN ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Yolanda, Yosi; Jasmi, Jasmi; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACTCylas formicarius is pest that damage of sweet potato plants. These pest damage part of tuber, stem and leaf. The form attack toward tuber of sweet potato, cause the tuber yet hollow, on leaf will cause leaf hollow, and the stem will look damage and easily wilt. Relative to the problem, than has done research with the title pest density Boleng population (Cylas formicarius) (Coleoptera: Curculiodae) on the sweet potato plants in Taluak Dalam at Kanagarian Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok. Using census sampling method in a way to make the square from measuring 1m x 1m. The result showed that the difference between stadia larva with stadia imago. The number of individuals on stadia larva is 256 tail/m² with andaverage 10,24/m², and then the number of individuals on stadia imago 177 tail/m² with and average 7,08/m². This can be regarded as pests because it resulted in decreased quality and production of sweet potato plants.